APLIKASI PELAYANAN KEPEGAWAIAN BERBASIS WEB BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SUMBAWA BARAT - Agus Jayadi; Erwin Fakhruddin (Jurnal Informatika Teknologi dan Sains, 2021)
The implementation of service provision and management of data and employee information has not been maximal. Employee information is only available if there is a request from internal and external parties. The research method used was a case study method for BKPSDM of West Sumbawa Regency, for the method of collecting data used were interviews, literature studies, and observations. The system development method was waterfall. After seeing the weaknesses of the running system, the application users are divided into four groups of users, they are SKPD operators, BKPSDM operators, employees and Super Admins. With the existence of e-Human Resources application, it is able to help and facilitate the tasks of General Administration and Employee Subdivision at SKPD in providing employee administration services to BKSDM or vice versa, including proposals for promotion, pension proposals, and proposals for moving work agencies (mutations) by online which is integrated so that the services are able to be effective and efficient.